2019
DOI: 10.1177/0269215519876299
|View full text |Cite
|
Sign up to set email alerts
|

Setting meaningful goals in rehabilitation: rationale and practical tool

Abstract: Context: Goal-setting is a key characteristic of modern rehabilitation. However, goals need to be meaningful and of importance to the client. Axioms: Both theories and empirical evidence support the importance of a hierarchy of goals: one or more overall goals that clients find personally meaningful and specific goals that are related to the overall goals. We posit that the client’s fundamental beliefs, goals and attitudes (“global meaning”) need to be explored before setting any rehabilitation goal. A chaplai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 29 publications
(35 reference statements)
2
48
0
1
Order By: Relevance
“…Previous studies on QOL in patients with LOPD mostly focused on the nancial and physical burdens presented by the disease; however, the humanistic aspect was largely overlooked. Dekker et al indicated that the painful processes of learning, coping, and adapting to disease-related psychology could induce a humanistic burden on the social capital and social support of the patients and their caregivers [10]. Our ndings indicated that promoting positive, successful interactions should be emphasized in improving QOL in patients with LOPD beyond the conventional emphasis on medication.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Previous studies on QOL in patients with LOPD mostly focused on the nancial and physical burdens presented by the disease; however, the humanistic aspect was largely overlooked. Dekker et al indicated that the painful processes of learning, coping, and adapting to disease-related psychology could induce a humanistic burden on the social capital and social support of the patients and their caregivers [10]. Our ndings indicated that promoting positive, successful interactions should be emphasized in improving QOL in patients with LOPD beyond the conventional emphasis on medication.…”
Section: Discussionmentioning
confidence: 71%
“…Despite the negative consequences of PD on physical health, ongoing and chronic illness stressors may induce emotional and cognitive adjustments to the disease. Some patients may handle the psychological burden of PD relatively well, while others may not [10]. Variations in the QOL of patients with LOPD were observed across countries and ethnicities.…”
Section: Introductionmentioning
confidence: 98%
“…Goal setting is an important element in modern rehabilitation and should include exploring the patients' global meaning (i.e., fundamental beliefs, goals and attitudes) after which a meaningful overall rehabilitation goal can be formulated (Dekker et al, 2020). After that, the patient and HCP can set specific rehabilitation goals to achieve the overall rehabilitation goal.…”
Section: Discussionmentioning
confidence: 99%
“…25 26 In contrast, service users emphasise broad, long-term goals that express their hopes and aspirations, prioritising goals related to non-medical concerns such as managing relationships, emotions and practical challenges such as housing and employment. 23 26 27 In addition, if the service user is assessed as experiencing severe mental health symptoms, they may be seen as lacking capacity, with practitioners less likely to involve them in shared decision-making processes. 19 28 While goal planning is increasingly being used within mental health service delivery, there is no clear understanding of the types of goals being set, experiences of service users and practitioners, or the effectiveness of goal planning as a mental health intervention.…”
Section: Open Accessmentioning
confidence: 99%